2019
DOI: 10.3389/fphar.2019.01002
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Inhibits IL-6 Transcription and Suppresses Esophageal Carcinogenesis

Abstract: Esophagus cancer is the seventh cause of cancer-related deaths globally. In this study, we analyzed interleukin 6 (IL-6) gene expression in human esophagus cancer patients and showed that IL-6 mRNA levels are significantly higher in tumor tissues and negatively correlated with overall survival, suggesting that IL-6 is a potential therapeutic target for esophagus cancer. We further demonstrated that apigenin, a nature flavone product of green plants, inhibited IL-6 transcription and gene expression in human eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Mechanistic studies have demonstrated that co-administration of apigenin and ABT-263 causes a decrease of AKT and ERK phosphorylation rate that reflects on FoxO3a transcription factor activity and, consequently, on the transcription of a member of Bcl-2 family protein, Noxa, that in turns activate caspase-3 [109]. Apigenin was also used in vivo in a xenograft mouse model and a reduction of tumor volume and weight was noted, confirming its potential role as a chemotherapeutic molecule [109,[113][114][115].…”
Section: Apigeninmentioning
confidence: 94%
“…Mechanistic studies have demonstrated that co-administration of apigenin and ABT-263 causes a decrease of AKT and ERK phosphorylation rate that reflects on FoxO3a transcription factor activity and, consequently, on the transcription of a member of Bcl-2 family protein, Noxa, that in turns activate caspase-3 [109]. Apigenin was also used in vivo in a xenograft mouse model and a reduction of tumor volume and weight was noted, confirming its potential role as a chemotherapeutic molecule [109,[113][114][115].…”
Section: Apigeninmentioning
confidence: 94%
“…Reduced cell viability and proliferation [359][360][361]. Induced cell cycle arrest at the G1 or G2/M phase [360,362,363].…”
Section: Apigeninmentioning
confidence: 99%
“…Apigenin + Abivertinib had synergistic anti-cancer effects [360]. Induced apoptosis and reduced angiogenesis [361].…”
Section: Apigeninmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin, Shi, Liu, Chen, and Yang (2019) showed that a new type of xanthones promoted HepG2 cell apoptosis through enhancing the expression of cleaved caspase‐8, caspase‐9, and caspase‐3. Qiu et al (2019) also found that apigenin inhibited cell proliferation and induced cell apoptosis by activating the caspase‐8 expression. Besides the proapoptosis function, recent studies showed the prosurvival effects of caspase‐8.…”
Section: Discussionmentioning
confidence: 97%